Mediterranean favorites (Taste of Home Books : RDA Enthusiast Brands, LLC., 2024)
Take your taste buds on a mouthwatering trip with Greek, Tuscan, Moroccan and other vibrant flavors inspired by the sun-kissed coastal region of the Mediterranean Sea.